2018
DOI: 10.18203/issn.2454-5929.ijohns20182953
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antibiotic sensitivity pattern in acute tonsillitis

Abstract: <p class="abstract"><strong>Background:</strong> The use of antibiotics against different pathogens in acute tonsillitis has been the general trend through the years. Penicillin has been the drug of choice for the management. But due to increased incidence of resistance in case of penicillin’s, other antibiotics are also used for the treatment of acute tonsillitis. The study was conducted with the objective to find out the antibiotic sensitivity and susceptibility pattern against microbial pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In our study two major gram-positive strains were found, that is, Streptococcus pneumonia (15) and S. aureus (17) and two gram-negative bacteria K. sepsis (23) and P. aeruginosa (19).…”
Section: Categorisation Based On Bacterial Strians Present In the Culturementioning
confidence: 63%
See 3 more Smart Citations
“…In our study two major gram-positive strains were found, that is, Streptococcus pneumonia (15) and S. aureus (17) and two gram-negative bacteria K. sepsis (23) and P. aeruginosa (19).…”
Section: Categorisation Based On Bacterial Strians Present In the Culturementioning
confidence: 63%
“…Ampicillin and amoxicillin, in both Streptococci and Staphylococci, showed poor sensitivity results. 18 Paired t test of sensitive and resistant drugs to grampositive bacteria showed a significant difference of p=0.0001 (p<0.05), that is the number of drugs resistant to the gram-positive bacteria is lesser than the number of drugs sensitive, while the same was not noted in gramnegative bacteria. 19,20…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Direct microscopy was done using the isolates from the culture media. 32 The culture and sensitivity was done at the Microbiology laboratory of University of Nigeria Teaching Hospital, Ituku-Ozalla, Enugu. The samples collected from Federal Medical Center, Umuahia, were put in ice pack and later refrigerated and sent in batches every 2 days (Wednesday and Fridays).…”
Section: Specimen Collectionmentioning
confidence: 99%